Differential antitumor activity of compounds targeting the ubiquitin-proteasome machinery in gastrointestinal stromal tumor (GIST) cells - Rausch, Jessica L.; Ali, Areej A.; Lee, Donna M.; Gebreyohannes, Yemarshet K.; Mehalek, Keith R.; Agha, Aya; Patil, Sneha S.; Tolstov, Yanis; Wellens, Jasmien; Dhillon, Harbir S.; Makielski, Kathleen R.; Debiec-Rychter, Maria; et al. (Scientific reports, 2020)
The majority of gastrointestinal stromal tumors (GISTs) are driven by oncogenic KIT signaling and can therefore be effectively treated with the tyrosine kinase inhibitor (TKI) imatinib mesylate. However, most GISTs develop imatinib resistance through secondary KIT mutations. The type of resistance mutation determines sensitivity to approved second-/third-line TKIs but shows high inter- and intratumoral heterogeneity. Therefore, therapeutic strategies that target KIT independently of the mutational status are intriguing. Inhibiting the ubiquitin-proteasome machinery with bortezomib is effective in GIST cells through a dual mechanism of KIT transcriptional downregulation and upregulation of the pro-apoptotic histone H2AX but clinically problematic due to the drug’s adverse effects. We therefore tested second-generation inhibitors of the 20S proteasome (delanzomib, carfilzomib and ixazomib) with better pharmacologic profiles as well as compounds targeting regulators of ubiquitination (b-AP15, MLN4924) for their effectiveness and mechanism of action in GIST. All three 20S proteasome inhibitors were highly effective in vitro and in vivo, including in imatinib-resistant models. In contrast, b-AP15 and MLN4924 were only effective at high concentrations or had mostly cytostatic effects, respectively. Our results confirm 20S proteasome inhibitors as promising strategy to overcome TKI resistance in GIST, while highlighting the complexity of the ubiquitin-proteasome machinery as a therapeutic target.
Gesehen am 22.10.2020